We are bitter, but we are better off: case study of the implementation of an electronic health record system into a mental health hospital in England - Takian Amirhossein; Sheikh Aziz; Barber Nicholas (BMC, 2012)
Abstract Background In contrast to the acute hospital sector, there have been relatively few implementations of integrated electronic health record (EHR) systems into specialist mental health settings. The National Programme for Information Technology (NPfIT) in England was the most expensive IT-based transformation of public services ever undertaken, which aimed amongst other things, to implement integrated EHR systems into mental health hospitals. This paper describes the arrival, the process of implementation, stakeholders' experiences and the local consequences of the implementation of an EHR system into a mental health hospital. Methods Longitudinal, real-time, case study-based evaluation of the implementation and adoption of an EHR software (RiO) into an English mental health hospital known here as Beta. We conducted 48 in-depth interviews with a wide range of internal and external stakeholders, undertook 26 hours of on-site observations, and obtained 65 sets of relevant documents from various types relating to Beta. Analysis was both inductive and deductive, the latter being informed by the 'sociotechnical changing' theoretical framework. Results Many interviewees perceived the implementation of the EHR system as challenging and cumbersome. During the early stages of the implementation, some clinicians felt that using the software was time-consuming leading to the conclusion that the EHR was not fit for purpose. Most interviewees considered the chain of deployment of the EHR-which was imposed by NPfIT-as bureaucratic and obstructive, which restricted customization and as a result limited adoption and use. The low IT literacy among users at Beta was a further barrier to the implementation of the EHR. This along with inadequate training in using the EHR software led to resistance to the significant cultural and work environment changes initiated by EHR. Despite the many challenges, Beta achieved some early positive results. These included: the ability to check progress notes and monitor staff activities; improving quality of care as a result of real-time, more accurate and shared patient records across the hospital; and potentially improving the safety of care through increasing the legibility of the clinical record. Conclusions Notwithstanding what was seen as a turbulent, painful and troublesome implementation of the EHR system, Beta achieved some early clinical and managerial benefits from implementing EHRs. The 'sociotechnical changing' framework helped us go beyond the dichotomy of success versus failure, when conducting the evaluation and interpreting findings. Given the scope for continued development, there are good reasons, we argue, to scale up the intake of EHR systems by mental health care settings. Software customization and appropriate support are essential to work EHR out in such organizations.